Autonomia e sottomissione. Hegel interprete dei drammi di Schiller - Pitillo, Federica (Filosofia Morale/Moral Philosophy, 2024)
This paper starts from the idea that Schiller, especially of the tragic phenomenon that allows in his mature dramas, presents a refined reflection of the tragic phenomenon, which allows us to rethink, with and beyond Hegel, the conflict between the individual and ethics, outlined in the Elements of the Philosophy of Right. More specifically, we will try to show how some of Schiller’s dramas can play a significant role in the construction of a Hegelian theory of passions. By analysing the concepts of revenge, guilt, crime and what we would today define as narcissism, we will see how Hegel attempts to base his theory of passions on the mediation – not always without opacity – between ancient and modern, fate and character, submission and autonomy.